Combination of general anesthesia and caudal block in laparoscopic surgery for neonates with annular pancreas: A case report - Putu Kurniyanta; Adinda Putri Antasari; Adinda Putra Pradhana (Bali Journal of Anesthesiology)
Abstract The annular pancreas is a rare congenital disorder that originates from the pancreas. It is believed to stem from an abnormal rotation of the ventral pancreatic bud as it wraps around the posterior side of the duodenum. While surgical corrections can be performed either through open surgery or laparoscopic methods, the latter is particularly challenging in neonates, especially when the surgery is complicated. One of the primary concerns with laparoscopic procedures in neonates is the potential for hemodynamic and respiratory changes. These changes arise mainly from the increased intra-abdominal pressure created by the pneumoperitoneum, which is essential for the laparoscopic approach. Furthermore, prolonged laparoscopic surgeries can induce an excessive stress response in neonates. To mitigate these challenges, a combination of general anesthesia and caudal block can be used. This approach not only ensures hemodynamic stability but also effectively reduces the neonate’s stress response.